2023
DOI: 10.1111/ene.15814
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping mitochondrial DNA‐related diseases in childhood: A cohort study of 150 patients

Abstract: Background and purpose: Mitochondrial diseases (MDs) are heterogeneous disorders caused by mutations in nuclear DNA (nDNA) or mitochondrial DNA (mtDNA) associated with specific syndromes. However, especially in childhood, patients often display heterogeneity. Several reports on the biochemical and molecular profiles in children have been published, but studies tend not to differentiate between mtDNA-and nDNA-associated diseases, and focus is often on a specific phenotype. Thus, large cohort studies specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…We found m.13094T>C (p.Val253Ala) in homoplasmy in P23, a mutation previously described associated with cerebellar syndromes [ 59 ], CI deficiency, or combined complexes deficiencies [ 60 ], presenting our patient a marked hypotonia. In pediatric populations, LSS appears to represent a less favorable prognosis [ 61 ]. P24 and P25 presented m.13513G>A (p.Asp393Asn), a mutation that has already been outlined by Ruiter et al in a patient with CI deficiency, cardiac rhythm perturbation, and optic atrophy [ 62 ], with our patients presenting cardiomyopathy and hypotonia, and ataxia and apnea, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We found m.13094T>C (p.Val253Ala) in homoplasmy in P23, a mutation previously described associated with cerebellar syndromes [ 59 ], CI deficiency, or combined complexes deficiencies [ 60 ], presenting our patient a marked hypotonia. In pediatric populations, LSS appears to represent a less favorable prognosis [ 61 ]. P24 and P25 presented m.13513G>A (p.Asp393Asn), a mutation that has already been outlined by Ruiter et al in a patient with CI deficiency, cardiac rhythm perturbation, and optic atrophy [ 62 ], with our patients presenting cardiomyopathy and hypotonia, and ataxia and apnea, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There is a discrepancy between the statement in the method section ("only few data were not available from all patients") and the results section ("CSF data were available from only 17 %, follow-up data only from 47%, and biochemical data only from 58 % of patients") [1]. This discrepancy should be clarified.…”
mentioning
confidence: 94%
“…With interest we read the article by Ardissone et al about a retrospective, singlecenter study of 150 pediatric patients with a genetically confirmed mitochondrial disorder (MID) due to a pathogenic mtDNA variant (mtDNA point mutation or single mtDNA deletion) [1]. The study is excellent but has limitations that are cause of concerns and should be discussed.…”
mentioning
confidence: 99%
See 2 more Smart Citations